2020
DOI: 10.3390/ijerph17051786
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Obesogenic Behaviors in Asian American Children with Immigrant and US-Born Mothers

Abstract: Child obesity is understudied in Asian Americans, which include a growing population of recent immigrants. We examined the relationship between maternal nativity and time in the US, and obesity and obesogenic behaviors among Asian American children. We analyzed public-use data from the 2013–2016 California Health Interview Survey for Asian American children ages 2 to 11 years. We used logistic regression to determine the odds of obesity and obesogenic behaviors associated with maternal nativity and time in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…In the present study, it was observed that children of immigrant origin showed higher levels of OW/OB than natives, and a higher adjusted risk of having OW/OB. This is consistent with other studies conducted in the United States [22], Europe [23,24], and Spain [25][26][27][28] which suggest that the immigrant origin of parents may be a risk factor in the development of excess weight in childhood. In Spain, there are several national studies on diet and childhood obesity [29,30], but they do not consider possible differences between natives and immigrants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, it was observed that children of immigrant origin showed higher levels of OW/OB than natives, and a higher adjusted risk of having OW/OB. This is consistent with other studies conducted in the United States [22], Europe [23,24], and Spain [25][26][27][28] which suggest that the immigrant origin of parents may be a risk factor in the development of excess weight in childhood. In Spain, there are several national studies on diet and childhood obesity [29,30], but they do not consider possible differences between natives and immigrants.…”
Section: Discussionsupporting
confidence: 92%
“…The choice of food type may also be determined by the availability and affordability of food in the family's immediate food environment [33,34]. Additionally, in different studies [22][23][24][25], socioeconomic status has been associated with the development of excess weight, with a higher prevalence of obesity being found in those with lower incomes, demonstrating data similar to those of the present study. Similarly, the present study shows that, for the same social class, overweight/obesity tends to be higher in children of immigrant origin.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, greater acculturation did not change their poorer health behavior (lower daily physical activity prevalence) in a positive direction. These findings generally support the “negative acculturation theory.” However, acculturation negatively influenced excess body weight only among Asian American boys, but not girls, which is in line with some prior study findings [ 38 , 39 ], but not all [ 40 ]. The sex difference in the acculturation effect could be due to the sex difference in the US cultural norms for body image: norms of muscularity for males and slimness for females [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…By incorporating community-based approaches to investigate biopsychosocial correlates of health, psychology has much to contribute to understanding variations in Asian American health not fully explained by demographic and health care access factors (Elewonibi et al, 2018; Ryu et al, 2013). Many understudied topics are also in need of psychological research (e.g., sleep [Hall et al, 2009] and eating behaviors [Argueza et al, 2020]), particularly using multilevel designs. Contributions from psychology also are needed to test and revise existing constructs and models (Hall et al, 2016) to increase knowledge for improving Asian Americans’ health.…”
Section: Recommendations For Demarginalizing the Health-related Needs...mentioning
confidence: 99%